Systemic Inducing Resistance on Cocoa Seedling Against Vascular Streak Dieback By Boron and Silikon Application - Fitria Yuliasmara; Sri Sukamto; A. Adi Prawoto (Indonesian Coffee and Cocoa Research Institute, 2011)
Black pod rot disease (BPRD) which is caused by Phytophthora palmivora is one of the main diseases of cocoa cultivations particularly in plantations with wet climate. Black pod rot can develop rapidly under high humidity environments, particularly during rainy seasons. This disease can cause loss of harvest of up to 46.63% in East Java. The various control efforts attempted so far have not resulted in significant improvements. Urea, in addition to functioning as fertilizer, can also produce the ammonia gas which is believed to be able to suppress black pod rot. This research aims to determine the effectiveness of black pod rot control using the combination of lime and urea. This research was conducted from June to September 2013. The materials used in test included sterile soil, black pod rot infected cocoa, urea, and agricultural lime. Observation results showed that ammonia could form from urea. Lime can increase the speed of the formation. The ammonia gas forming from 0.06% urea and 0.3% lime can control the P. palmivora fungus inside the soil. Key words: Pod rot, P. palmivora, urea, lime, ammonia